2017
DOI: 10.1111/itor.12399
|View full text |Cite
|
Sign up to set email alerts
|

Model and algorithm for bilevel multisized terminal location‐routing problem for the last mile delivery

Abstract: The last mile delivery is regarded as one of the most expensive but least efficient stretches in the businessto-customer supply chain. Designing the last mile delivery system in a lean way is crucial to serve customers efficiently and economically. To address this issue, we propose a bilevel multisized terminal location-routing problem (BL-MSTLRP) with simultaneous home delivery and customer's pickup services. The solution method is proposed by combining genetic algorithm (GA) and simulated annealing (SA), cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 58 publications
0
44
0
Order By: Relevance
“…Scheduling focuses on planning the sequence of deliveries in the last mile, including delivery scheduling [112,114] and drone scheduling [113]. Facility location includes articles concerned with the placement of facilities for last mile logistics [120,121].…”
Section: Themes In Last Mile Logisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scheduling focuses on planning the sequence of deliveries in the last mile, including delivery scheduling [112,114] and drone scheduling [113]. Facility location includes articles concerned with the placement of facilities for last mile logistics [120,121].…”
Section: Themes In Last Mile Logisticsmentioning
confidence: 99%
“…Facility location Location routing and its impacts on the distribution system [118][119][120][121]. 4…”
Section: Schedulingmentioning
confidence: 99%
See 1 more Smart Citation
“…Xuefeng et al suggested a multi-objective location-routing problem with simultaneous pick-up and delivery [9]. Zhou et al proposed a bi-level multi-sized terminal location-routing problem with simultaneous home delivery and customer pickup [10]. Regarding market density or demand for delivery services, Felisberto et al introduced recipient pricing in the postal sector and tested with Swiss post data by considering the area and the amount of congestion [11].…”
Section: Last Mile Deliverymentioning
confidence: 99%
“…The objective Function (9) represents the sum of incremental profit obtained through collaboration. Constraint (10) assures that only one service center can be selected for the last mile delivery service in each service region. Constraint (11) implies that the number of service regions should belong to the controlled range.…”
Section: Model Formulationmentioning
confidence: 99%